Evaluation of serum folate level before and after bath PUVA therapy in patients referred to Razi Hospital, Rasht, Iran. Issue 5 (28th June 2019) - Yousefkhani, Leila; Rafiei, Rana; Darjani, Abbas; Alizadeh, Narges; Eftekhari, Hojat; Gharaei Nejad, Kaveh; Rafiei, Elahe; Rafiee, Behnam
Abstract: Ultraviolet (UV) radiation could disintegrate folate molecule, so phototherapy may reduce folate levels in the patients. The effect of phototherapy on serum folate in human body is questionable. We investigated the effect of bath PUVA therapy on serum folate level. This study was designed as a before–after study. Thirty‐two patients completed study during 2 years. Our variables were demographic data, folate levels before and 8 weeks after treatment and cumulative dosage of UVA during 8 weeks of treatment. Serum folate was evaluated with chemiluminescence immunoassay technique. All data were analyzed using SPSS 18 software. Folate level changes were statistically significant before and after bath PUVA therapy. There was no significant difference in folate levels in psoriasis patients compared with nonpsoriasis patients. In psoriasis patients, folate levels had no significant correlation with psoriasis activity index before treatment. Decrease in folate levels was more significant in fair‐skinned patients. There was no association between folate status and cumulative dosage of UVA. Bath PUVA therapy reduced serum folate level in our patients although none of them were folate deficient. Folate deficiency should be evaluated and corrected especially in fair‐skinned cases, as it may be aggravated by phototherapy.